Análisis y Simulación del protocolo HIERARCHICAL MOBILE IPV6 en el enrutamiento usando Network Simulator NS - Aguilar Vega, Verónica Katherine (2019)
Mobility management is studying according to two protocols: macro mobility with MIPV6 (Mobility Support IPV6) (Johnson, Arkko, & Perkins, 2004) and micro-mobility with HMIPV6 (Hierarchical Mobile IPV6) (Soliman, Castelluccia, El Malki, & Bellier, 2005). At present, HMIPV6 (Soliman, Castelluccia, El Malki, & Bellier, 2005), is considered an extension of the MIPV6 protocol (Johnson, Arkko, & Perkins, 2004), because it examines the shortcomings of macro mobility, then this experimental protocol for the Internet community is a reference for this research to correct the various problems in mobile communications, in this way benefits are providing with respect to the decrease of the terms of delivery speed, bandwidth, and improvement in the quality of the service. Because of this circumstances, the main objective of this investigation is to analyze and simulate the HMIPV6 protocol (Soliman, Castelluccia, El Malki, & Bellier, 2005), with the specifications of the RFC (Request For Comments) (Francois & Villagomez, 2018) 4140. This simulation is implemented in the NS-3 software (Network Simulator version 3) (NSNAM, 2011), because it is an ideal software to perform simulations of fixed and wireless networks. With the NS-3 software,'you can verify the simulation information, using two tools: visualization of the simulation graph with the NetAnim tool, while the Tracemetrics tool analyzes the Throughput, delivery speed, average time spent by each packet in the node, number of packages sent, lost and redundant packets.